Corrosion Inhibition of Zinc Metal in Hydrochloric acid Solution by Using Ciprofloxacin Drug as an Inhibitor - Bedran, Osama; Al-Maamar, Ali; Zageer, Dheaa; Yousif, Emad (Al-Nahrain Journal of Science, 2018)
The corrosion of zinc in 4 M HCl by has been investigated at room temperature, and at different temperatures using weight loss measurements, and inhibited by using ciprofloxacin drug. Results obtained showed that ciprofloxacin is a convenient inhibitor and its inhibition efficiency (IE %) increased with the increase of inhibitor concentration. The best temperature which showed the lowest corrosion rate values was at 318K.The mechanism of adsorption had been explained on the basis of chemical structure of the investigated inhibitor. It was found that the protection of zinc metal using this corrosion inhibitor is not complicated at room temperature, and the optimum concentration of inhibitor has been calculated which had showed the maximum surface coverage.